ENGLISH IN INSTITUTIONS OF PRESCHOOL EDUCATION - Usmonova, Umida (Maktabgacha taʼlim jurnali, 2021)
For the world that is changing greatly is now forging the use of many more languages , in addition to its native tongue . The present article outlines the need to organize traditional courses based on a new approach to preschool education, the need to teach English from the first young people, and the development of language skills through various games, as well as more effective methods.